Question
\( 1 \leftarrow \begin{array}{l}\text { Solve the formula for } t \text {. } \\ \qquad=3 \pi z t+3 \pi z^{2} \\ t=\square\end{array} \)
Ask by Summers Evans. in the United States
Feb 04,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( t = \frac{1 - 3\pi z^{2}}{3\pi z} \)
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Unlock
Reviewed and approved by the UpStudy tutoring team
Like
Mind Expander
To solve the formula for \( t \), we start with the equation: \[ 1 = 3 \pi z t + 3 \pi z^2 \] First, isolate the term containing \( t \) by subtracting \( 3 \pi z^2 \) from both sides: \[ 1 - 3 \pi z^2 = 3 \pi z t \] Next, divide both sides by \( 3 \pi z \): \[ t = \frac{1 - 3 \pi z^2}{3 \pi z} \] So the solution for \( t \) is: \[ t = \frac{1 - 3 \pi z^2}{3 \pi z} \]